STOCK COMPANIES FROM THE PERSPECTIVE OF ISLAMIC ECONOMICS IN INDONESIA - Danil Danil; Rahma Helal Al_ Jbour; Hydzulkifli Bin Haji Hashim (Review of International Economy and Finance, 2024)
This study is intended to explore the relationship between company data and stock performance, particularly in the realm of Indonesia's Islamic economy. The main focus of this research is on stock corporations that operate in compliance with the principles of Islamic economics. The main data sources are sourced from company financial data as well as stock price data involving a specific research time. The research method applied is a qualitative approach through literature study. The research found that information sourced from financial statements plays a crucial role in shaping stock performance. In particular, this information has a significant impact on the stock performance of Islamic companies. In addition, aspects of Islamic economics, such as fairness and transparency, also play an important role in maintaining the integrity and trust of investors in the company. Thus, this study contributes to a deeper understanding of the essential relationship between corporate information and stock performance, opening new perspectives in the context of Islamic economics in Indonesia.